2022
DOI: 10.1136/openhrt-2022-002200
|View full text |Cite
|
Sign up to set email alerts
|

Coronary endothelial dysfunction: from pathogenesis to clinical implications

Abstract: Endothelial dysfunction (ED) has a substantial role in the pathogenesis of atherosclerosis and other vascular diseases. Multiple risk factors, including smoking, hyperlipiadaemia and diabetes, can have associated ED, which is correlated with cardiac events. Measurement of coronary artery endothelial function requires the use of invasive techniques to assess both epicardial coronary artery and microvascular beds. Peripheral vascular techniques and endothelial biomarkers can be used to indirectly assess coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
(94 reference statements)
0
2
0
1
Order By: Relevance
“…EPA and DHA modulate some of the most important known risk factors of CAD, such as blood lipids, blood pressure, heart rate, heart rate variability, platelet aggregation, inflammation, and endothelial function [ 6 ]. Of particular interest, endothelial dysfunction is one of the earliest events in the pathological development of atherosclerotic diseases [ 6 , 7 ]. Accordingly, prospective studies have shown that flow-mediated dilation (FMD), the gold standard for measuring endothelial dysfunction in vivo, is an independent predictor of cardiovascular events, such as heart attack or stroke [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPA and DHA modulate some of the most important known risk factors of CAD, such as blood lipids, blood pressure, heart rate, heart rate variability, platelet aggregation, inflammation, and endothelial function [ 6 ]. Of particular interest, endothelial dysfunction is one of the earliest events in the pathological development of atherosclerotic diseases [ 6 , 7 ]. Accordingly, prospective studies have shown that flow-mediated dilation (FMD), the gold standard for measuring endothelial dysfunction in vivo, is an independent predictor of cardiovascular events, such as heart attack or stroke [ 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, endothelial dysfunction is one of the earliest events in the pathological development of atherosclerotic diseases [ 6 , 7 ]. Accordingly, prospective studies have shown that flow-mediated dilation (FMD), the gold standard for measuring endothelial dysfunction in vivo, is an independent predictor of cardiovascular events, such as heart attack or stroke [ 6 , 7 , 8 , 9 , 10 , 11 ]. Therefore, therapies targeted to improve endothelial dysfunction, such as EPA and DHA supplementation, may report important benefits to subjects at risk of CAD.…”
Section: Introductionmentioning
confidence: 99%
“…Прогресування ІХС і розвиток стенокардії високих ФК супроводжується дисбалансом у системі вазодилатуючих і вазоконстрикторних ендотеліальних чинників, які визначають тонус гладком'язових клітин судин і відіграють важливу роль у формуванні її клінічного перебігу [5, 21,22].…”
Section: результати дослідження та їх обговоренняunclassified
“…This score is based on parameters that reflect the patient's nutritional and inflammatory status and is based on total cholesterol, albumin, lymphocyteto-monocyte ratio (LMR), and neutrophil-lymphocyte ratio (NLR) [1,2]. Many studies have shown that low albumin, high cholesterol, and chronic inflammation are related to an increased risk of coronary slow flow phenomenon (CSFP) as early stage of coronary artery disease [3][4][5]. The combination of these risk factors corresponds to the NPS parameters except the cholesterol level.…”
Section: Introductionmentioning
confidence: 99%